Plasmonic Metasurfaces: An All‐Optically Controlled Liquid‐Crystal Plasmonic Metasurface Platform (Laser Photonics Rev. 14(11)/2020). Issue 11 (12th November 2020) - Sharma, Mukesh; Ellenbogen, Tal
Abstract : In article number 2000253, Mukesh Sharma and Tal Ellenbogen demonstrate an all‐optically controlled liquid‐crystal plasmonic metasurface platform. Laser‐induced thermo‐optical nematic‐to‐isotropic phase transition enables polarization switching in a twisted‐NLC layer. It is used to locally modify the interaction with the metasurface and to switch the color of transmitted and reflected light.